Uncovering Patterns: LEPT Performance of Secondary Takers of Father Saturnino University for Curricular Enhancement - Floreta, Arlyn M.; Hallazgo, Rheomie O.; Pinedo, Alvin C. (Randwick International of Education and Linguistics Science Journal, 2025)
This study examines the Licensure Examination for Teachers (LEPT) performance of secondary test-takers from Father Saturnino Urios University (FSUU), distinguishing between education and non-education graduates. Covering four examination periods from January 2022 to March 2024, it employs a descriptive-correlational design using secondary data from the Professional Regulation Commission (PRC). Descriptive and inferential statistical methods, including T-tests, Pearson’s correlation coefficient, and One-Way ANOVA, were used to analyze participation and performance patterns. Findings indicate that graduates from programs closely aligned with the Bachelor of Secondary Education (BSEd) curriculum and corresponding LEPT majors generally performed well. No significant differences were found between unit earners from Nursing and Accountancy compared to Teacher Education Program (TEP) takers. However, significant differences emerged in the performance of Business Administration and Computer Studies graduates compared to TEP takers. Time elapsed between graduation and taking the LEPT was shorter among passers, though no direct correlation was found between time since graduation and licensure performance. Instead, the time since completing the required 18 professional education units appeared more influential. Furthermore, no significant differences in LEPT performance were observed across the four examination periods, indicating stable performance trends. To improve licensure outcomes, the study suggests offering a Teacher Certificate Program, strengthening alumni support, implementing early intervention programs, and integrating a licensure review component into the curriculum, particularly for non-education graduates. These strategies aim to enhance test preparedness and support students in obtaining professional teaching certification.